Polyethylene microplastics adversely affect airway patency - Shamsul Anuar, Nurshafida Adzlin; Pang, Li-Yin; Selvam, Sivathass Bannir; Gibbins, Christopher Neil; Kang Nee, Ting (Life Sciences, Medicine and Biomedicine, 2022)
Human exposure to microplastics through inhalation has been widely reported in recent years. There is a paucity of work focusing on the direct effect of accumulation of microplastics in airways and how it may impact the respiratory function. This study aimed to investigate whether the exposure of microplastic would change the contractility of isolated airway smooth muscle tissue. Microplastics were obtained through milling of high-density polyethylene (HDPE) pellets by using a centrifugal mill. To confirm that the milled microplastic particle size range fell within the definition of microplastic, field-emission scanning electron microscope (FESEM) was employed. The milled microplastics particle size ranged from 44.2 µm to 552.4 µm. The organ bath technique was employed to study the direct change of tissue contractility of rat isolated tracheal rings. Tracheal rings were incubated with polyethylene microplastics of different concentrations (0.3 mg/ml to 10 mg/ml) for a minimum of 18 hours in physiological Krebs buffer, followed by the construction of concentration-response curves to a contractile agent, carbachol (muscarinic agonist). Exposure to all concentrations of polyethylene microplastics enhanced the contractile responses of the tissues to carbachol. However, the effect was only statistically significant in tissues incubated at 3 mg/ml and above (p < 0.05). Findings from this study provide preliminary evidence that exposure to polyethylene microplastics adversely affects airway function. Heightened contractile responses of airways mimic the pathophysiological responses in respiratory diseases such as asthma, chronic cough and chronic obstructive pulmonary disease. Further experiments focusing on the possible mechanism of actions of these microplastics affecting the airway tissue function are now needed.